Risk factors of breast cancer among Iraqi women - Abedalrahman, Sarab K.; Ali, Besmah M.; Al-Khalidy, Najim Abid Issa; Al-Hashimi, Ali S. (Journal of Contemporary Medical Sciences, 2019)
Objectives: This study aimed to identify the risk factors of Breast Cancer among Iraqi women. Methods: A retrospective case control study, done on 147 breast cancer cases compared with 161 non- malignant cases selected randomly from women health center in Al-Elwyia maternity teaching hospital. Results: increased risk for breast cancer significantly associated with increased age especially ≥ 60 years, widow or divorced women(OR 3.7, CI (1.5-8.5)), menopause ((OR 6.43, CI(3.58-11.9)),age at menarche < 12 years (OR 1.99, CI (1.04-3.8)), and use of contraceptive pills for≥ 1 year (OR 1.99, CI (1.01-3.95)). Conclusion: positive risk factor for breast cancer was old age≥ 60 years, widow or divorced women, menopause, age at menarche < 12 years, and use of contraceptive pills for≥ 1 year. Family history, 2nd degree relative, not associated with breast cancer. There are some discrepancies between our findings and other studies in the literature need further studies.